Overexpression of Arabidopsis BBX 21 Gene in Bg 250 Rice Enhances Its Architecture and Productivity - Ratnayaka, R.M.L.K.; Jayasekera, G.A.U.; Hettiarachchi, G.H.C.M. (International Journal of Applied Sciences and Biotechnology, 2016)
Arabidopsis BBX21 protein was identified as a transcription activator which can activate the light dependent transcription and positively regulate light mediated development of plants. The productivity of crop plants can be enhanced by over-expressing central regulators of light signaling pathway. The present study was conducted to enhance the productivity of Bg 250 Sri Lankan rice variety by overexpressing Arabidopsis BBX21 gene. The BBX21 gene was cloned into pPZP 200 binary vector and the cloned vector gene construct was transformed into Agrobarcteium tumefaciens GV3101 strain by freeze thaw method. The selected recombinant colonies of A. tumefaciens strain GV3101 harboring BBX 21 gene were transformed into three weeks old Bg 250 rice callus. Selection of the transformed callus was conducted on N6B5 selection medium containing 50 mg/L gentamycin and 500mg/L cefotaxime. A total of putative 83 plants which showed resistant to gentamycin were subjected to PCR analysis and the results showed 69 of the regenerated plants are transgenic. The T1 seeds collected from putative transgenic plants were characterize to check its integration and inheritance. The transgenic plants which showed 3:1 ratio was selected and further grown to obtain its homozygous lines. The expression of BBX21 gene was demonstrated by northern blot analysis and the results showed 4 fold higher expression of BBX21 gene in the transgenic plants compared with its non-transgenic wild type plants. The phenotypic analysis of homozygous BBX21 transgenic plants showed improved plant height, leaf length, leaf area, number of panicles and bushy appearance compared with its non-transgenic plants. Taken together, these results demonstrate an involvement of BBX21 gene in rice modifying architecture and productivity of Bg 250 transgenic plants. Int J Appl Sci Biotechnol, Vol 4(2): 240-246